2009
DOI: 10.1111/j.1442-9993.2009.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of birds and bees in the pollination of Metrosideros excelsa (Myrtaceae)

Abstract: Exclusion experiments were used to assess the effect of different pollinator groups on outcrossing and seed production in Metrosideros excelsa. The main study site was Little Barrier Island, New Zealand where indigenous bird and native solitary bees are the main flower visitors. Our results showed that native birds were more important pollinators of M. excelsa than native bees. Seed production was much higher in open pollination than in two exclusion experiments where either birds were excluded and native bees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
(61 reference statements)
3
16
0
Order By: Relevance
“…Previous studies have suggested that M. excelsa and K. excelsa are specialized for bird pollination on the basis of copious nectar production, the size of floral parts [25] and, in the case of M. excelsa, exclusion experiments [39]. However, the continued presence of these species at North Island sites where most native bird pollinators are absent has been suggested as evidence that invertebrates may be adequate pollinators [25].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies have suggested that M. excelsa and K. excelsa are specialized for bird pollination on the basis of copious nectar production, the size of floral parts [25] and, in the case of M. excelsa, exclusion experiments [39]. However, the continued presence of these species at North Island sites where most native bird pollinators are absent has been suggested as evidence that invertebrates may be adequate pollinators [25].…”
Section: Discussionmentioning
confidence: 81%
“…The importance of mammal-mediated pollination in New Zealand may have been overlooked because most previous pollination studies either ignored the shorttailed bat or regarded it as an incidental flower visitor [24,25,39], despite reports of nectar-feeding behaviour and pollen in guano [45 -48]. As a consequence, the potential role of introduced mammals in maintaining pollination function for native plant species has not been seriously considered previously [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Native birds are more important pollinators of M. excelsa than native bees because of their greater abundance, larger body sizes and foraging patterns which are more efficient at inducing seed set and promoting outcrossing. Similarly, introduced honeybees are more effective pollinators than native bees because their larger body size promotes stigma contact (Schmidt-Adam et al 2009). Nocturnal visitation by New Zealand's endemic geckos (Whitaker 1987) and short-tailed bat (Mystacina tuberculata) has also been reported (Arkins et al 1999;Pattemore & Biological flora of New Zealand 373…”
Section: Plant-pollinator Relationshipsmentioning
confidence: 98%
“…DEP conducted fieldwork in 2008and 2009 , and SHA conducted fieldwork in 2005and 2009. We thank the tribes Ngati Wai and Kawerau-A-Maki for permission to undertake this research in areas of importance to them.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Schmidt-Adam et al 2009;Anderson et al 2011;Pattemore & Wilcove 2012). The existence of island refuges that retain populations of bird species now locally extinct on the main North and South Islands affords an opportunity to compare pollination processes before and after pollinator loss (e.g.…”
Section: Introductionmentioning
confidence: 99%